2016
DOI: 10.1111/jnc.13606
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of riluzole as a potential therapeutic drug for spinocerebellar ataxia type 3

Abstract: Spinocerebellar ataxia type 3 (SCA3) is an autosomal dominantly inherited neurodegenerative disorder for which no curative therapy is available. The cause of this disease is the expansion of a CAG repeat in the so-called ATXN3 gene leading to an expanded polyglutamine stretch in the ataxin-3 protein. Although the function of ataxin-3 has been defined as a deubiquitinating enzyme, the pathogenic pathway underlying SCA3 remains to be deciphered. Besides others, also the glutamatergic system seems to be altered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 61 publications
(68 reference statements)
0
27
0
Order By: Relevance
“…Transgenic animals were identified by using DNA extracted from ear biopsy (Roche High Pure PCR Template Preparation Kit; Roche) as described in ref. 6 (Table S6).…”
Section: Methodsmentioning
confidence: 99%
“…Transgenic animals were identified by using DNA extracted from ear biopsy (Roche High Pure PCR Template Preparation Kit; Roche) as described in ref. 6 (Table S6).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, a larger and longer study demonstrated no effect of riluzole in HD patients, suggesting that riluzole treatment may not useful in these patients. Postsymptomatic treatment of a conditional mouse model of MJD/SCA3 with riluzole led to no improvement of the motor uncoordination; intriguingly, riluzole chronic administration decreased the Calbindin expression in Purkinje cells of the cerebellum, suggesting possible toxicity . In contrast, a randomized clinical trial in SCA patients of different etiologies showed the short‐term efficacy (4 and 8 weeks) of riluzole in reducing disease symptoms.…”
Section: Therapeutic Strategies For Polyq Diseasesmentioning
confidence: 95%
“…Furthermore, the anti-glutamatergic compound riluzole was identified to improve ataxia symptoms in a randomized, double-blind, placebo-controlled pilot trial with 40 ataxia patients of different etiologies [ 188 ]. Given the proposed role of glutamatergic signaling for the induction of toxicity in SCA3 [ 49 ], riluzole was assessed in a SCA3 mouse model [ 128 ]. However, treatment with riluzole in the drinking water during 10 months did not provide an improvement in the rotarod performance, home cage activity, or body weight [ 128 ].…”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…Given the proposed role of glutamatergic signaling for the induction of toxicity in SCA3 [ 49 ], riluzole was assessed in a SCA3 mouse model [ 128 ]. However, treatment with riluzole in the drinking water during 10 months did not provide an improvement in the rotarod performance, home cage activity, or body weight [ 128 ]. Surprisingly, riluzole-treated animals showed a higher number of damaged Purkinje neurons.…”
Section: Pharmacological Therapiesmentioning
confidence: 99%